Homenaje a Alejandro Mina - Ordorica, Manuel; Echarri Cánovas, Carlos Javier; Giorguli, Silvia E.; Rodríguez Abreu, Mauricio (El Colegio de México A.C., 2019)
El Colegio de México paid tribute to Alejandro Mina, an outstanding demographer and teacher of many generations of population students. The posthumous act was held on February 6, 2019 in the Alfonso Reyes Hall of this institution. The addresses of the speakers are reproduced below in order of appearance: Manuel Ordorica, research fellow at the Center for Demographic and Urban Studies (CEDUA) of El Colegio de México; Carlos Javier Echarri Cánovas, research fellow at CEDUA, El Colegio de México and general secretary of the National Population Council; Silvia E. Giorguli, president of El Colegio de México; and Mauricio Rodríguez Abreu, professor at the University of the Americas, Puebla. The act was moderated by Jaime Sobrino, director of CEDUA, El Colegio de México.